Permeation of probe molecules into alginate microbeads: Effect of salt and processing. (December 2017) - van Leusden, P.; den Hartog, G.J.M.; Bast, A.; Postema, M.; van der Linden, E.; Sagis, L.M.C.
Abstract: The ability to exclude harmful factors from a hydrogel microbead is important for the degree of protection the beads offers to what is encapsulated within. The permeability of alginate microbeads, prepared by water-in-oil emulsification, was investigated by their ability to exclude FITC-labelled protein probes. The influence of alginate concentration, calcium concentration and method of addition, and salt content of the environment was investigated. The permeability was also compared to the permeability of beads made by the traditional method of dripping an alginate solution into a CaCl2 solution. Beads produced with low amounts of CaCl2 show a significant degree of swelling and are therefore very permeable (C/C0 (BSA) = 0.62, where C is the final concentration of BSA-FITC in the bead, and C0 the concentration of BSA-FITC in the continuous phase). With additional calcium, either by adding more calcium crystals after the emulsification step or by washing with a CaCl2 solution, beads swell less and are less permeable (C/C0 (BSA) = 0.13 and 0.12). Beads made by dripping are very permeable (C/C0 (BSA) ∼ 0.60). Because in this process the droplets of alginate are not constrained by a water-oil boundary, the beads can swell during gelation. The salt concentration in the continuous phase influences the strength of the electrostatic repulsion between the probes and the alginate network and hence affects the permeation of the probes into the beads. In the absence of salt, even FITC (389Da) is mostly excluded from the interior of the beads (C/C0 (FITC) ∼ 0.09). Graphical abstract: Highlights: Calcium concentration influences the swelling and permeability of alginate beads. Method of calcium addition to alginate influences microstructure and permeability. Beads made by dripping are more permeable than beads made by emulsification. When salt is absent even small molecules can be excluded from an alginate network.